Collective defined contribution plans: Backtesting based on German capital market data 1950-2022 - Oskar Goecke (Technische Hochschule Köln, Institut für Versicherungswesen (ivwKöln), 2022)
Using historical capital market data for Germany (1950-2022) we analyze and compare (individual) defined contribution (IDC-) and collective defined contribution (CDC) pension plans. To this end we define simple asset liability management rules that govern a CDC pension plan and compare these to IDC-plans with the same asset allovation. Our main result is, that the CDC pension plans allow for a significant improvement of the risk return profile compared to individual pension plans. Hereby we consider different risk measures. This empirical study affirms the theoretical results based on stochastic CDC-models.
urn:nbn:de:hbz:832-cos4-9875
Keywords: G; G2; G20; 330